2020
DOI: 10.1088/1402-4896/ab4d2a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of Mn-doped CaWO4 nanoparticles

Abstract: Pure and Mn-doped calcium tungstate (Mn:CaWO4) nanoparticles (NPs) were synthesized by hydrothermal method which lead to the formation of high quality and narrow sized particles. The concentration of Mn in CaWO4 NPs was varied from 1% to 4% by weight. A distinct peak of Mn (d–d) transition was observed which is actually spin-forbidden but may be allowed due to crystal field effects. Electron spin resonance measurements revealed inclusion of Mn2+ at the substitutional site.. Room temperature photoluminescence e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Pereira et al [13] suggested SrWO 4 :Eu 3+ phosphors for the applications of red emitting devices with an exciting wavelength of 393 and 462 nm. After that, Suneeta et al [14] synthesized the nanoparticles of Mn-doped calcium tungstate (CaWO 4 ) materials through hydrothermal method having 530 nm orange emission which corresponded to thesp dlevel transitions. Feng et al [15] stated that a series of BaWO 4 :Eu 3+ were prepared by the co-precipitation/calcination method.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al [13] suggested SrWO 4 :Eu 3+ phosphors for the applications of red emitting devices with an exciting wavelength of 393 and 462 nm. After that, Suneeta et al [14] synthesized the nanoparticles of Mn-doped calcium tungstate (CaWO 4 ) materials through hydrothermal method having 530 nm orange emission which corresponded to thesp dlevel transitions. Feng et al [15] stated that a series of BaWO 4 :Eu 3+ were prepared by the co-precipitation/calcination method.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds formulated as MWO 4 (M: bivalent cation) are known as tungstate and have been utilized in various applications like luminescence, photocatalytic, laser, optoelectronics, next generation of cryogenic phonon-scintillation detectors [1][2][3][4]. The crystal structure of MWO 4 compounds formed by large M 2+ cations like Ca, Ba and Pb is tetragonal scheelite structured [5]. One of the members of this family is lead tungstate (PbWO 4 ) having tetragonal scheelite structure with lattice parameters of a=b=5.456 Å and c=12.020 Å [6].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Particularly, this material activated with transition metal (TM) ions for unique optical and laser properties has a wide range of practical applications, such as scintillators for detecting X-rays and γ-rays in medical fields. [7][8][9] The above properties are sensitively related to the local structures around the dopant ions in the hosts; thus, it is necessary to explore the exact nature of the local structure associated with cation impurities. Since electron paramagnetic resonance (EPR) technology has long been considered as an effective tool for investigating the site symmetry and the dynamic behavior of TM ions in crystals, the local structures around TM impurities, which usually act as the paramagnetic probes, can be analyzed by means of the EPR technique.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Till now, extensive studies have been carried out on the defect structures and interactions between impurity and ligands, such as Cu 2+ , Fe 3+ , Mn 2+ , Cr 3+ , and Co 2+ ions in CaWO 4 , with EPR experimental technique and the theoretical analysis based on the crystal field (CF) theory. [7,[13][14][15] Among these TM ions, copper (Cu 2+ ) ions having 3d 9 configuration are widely used as paramagnetic probes due to merely a single ground state and a single excited state under ideal octahedral CFs. For example, Lynch [15] measured the EPR spectra of Cu 2+ doped CaWO 4 crystal and found that Cu 2+ occupies the host W 6+ site.…”
Section: Introductionmentioning
confidence: 99%